Beyond torture checklists: an exploratory study of the reliability and construct validity of the Torturing Environment Scale (TES) - Pau Pérez-Sales; Raquel González-Rubio; Blanca Mellor-Marsá; Gonzalo Martínez-Alés (BMC, 2021)
Abstract Background Torture methods have traditionally been quantified using checklists. However, checklists fail to capture accurately both the almost infinite range of available methods of torture and the victims' subjective experience. The Torturing Environment Scale (TES) was designed as a multidimensional alternative that groups torture methods according to the specific human function under attack. This study aims to do an exploratory assessment of the internal consistency reliability and discriminatory validity of the TES as part of a construct validity assessment in a sample of Basque torture survivors. Methods We applied the TES to a sample of 201 torture survivors from the Istanbul Protocol Project in the Basque Country Study (IPP-BC) to profile torturing environments in detention. To estimate the internal consistency reliability of the scale, categorical omega values were obtained for each subscale of the TES. To assess its discriminatory validity, the "known groups" method was used comparing mean scorings by gender, state security forces involved in the detention, and decade (the 1980s to the present) when the events took place. Results Men reported more physical pain, while women reported more attacks on self-identity and sexual integrity. The TES also showed significant differences as regards the security forces involved in the detention: Civil Guard (a militarised police) used more manipulation of the environment, threats, fear, pain and extreme pain, as compared to national and regional corps. Finally, although patterns of torture remained mostly unchanged across decades, more recent detentions included more emphasis on psychological attacks: context manipulation, humiliation linked to sexual identity, and attacks to meaning and identity. For all subscales of the TES, categorical omega values ranged from 0.44 to 0.72. Conclusion The TES may be a useful tool in profiling torturing environments. Its sensitivity to key contextual variables supports the discriminatory validity of the scale. While some of the subscales showed an acceptable degree of internal consistency, others require further analysis to improve reliability. The scale provides unique insights into the profile of contemporary torture. It will allow for future quantitative research on the relationship between different torturing environments and the medical and psychological consequences thereof.